The Role of Token Economy in Reducing Procrastination Among Active Organizational Students - Syah, Moch. Irwan; Abdurrahman, Ahmad Hammam; Jamaluddin, Muhammad (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Academic procrastination is a common maladaptive behavior among university students, especially those active in organizations who must balance academic and extracurricular responsibilities. Objective: This study aimed to examine the effectiveness of the token economy technique in reducing academic procrastination among organizational students at UIN Maulana Malik Ibrahim Malang. Method: Employing a one-group pretest-posttest experimental design, 16 purposively selected students participated in a three-week intervention involving structured rewards such as E-Wallet balances and mentoring services. The Academic Procrastination Scale–Short Form (APS-S) was used for data collection, while the analysis of the research results used gain score and paired sample t-test with JASP software. Results: The results showed a significant reduction in procrastination scores from pretest (M=81.88) to posttest (M=67.81), with p < 0.001. Conclusion: These findings suggest that token economy, when supported by time management strategies like the Eisenhower Matrix and social reinforcement, can effectively motivate students to complete academic tasks on time. This approach not only modifies behavior but also enhances self-regulation and responsibility in organizational contexts. Abstrak Latar Belakang: Penundaan akademik (academic procrastination) adalah perilaku maladaptif yang umum terjadi di kalangan mahasiswa, terutama yang aktif dalam organisasi dan harus menyeimbangkan tanggung jawab akademik dan ekstrakurikuler. Tujuan: Penelitian ini bertujuan untuk menguji keefektifan teknik token economy dalam mengurangi penundaan akademik pada mahasiswa yang aktif berorganisasi di UIN Maulana Malik Ibrahim Malang. Metode: Menggunakan desain eksperimen one-group pretest-posttest, 16 mahasiswa yang dipilih secara purposif mengikuti intervensi selama tiga minggu dengan struktur hadiah seperti saldo E-Wallet dan layanan mentoring. Alat pengumpulan data menggunakan Academic Procrastination Scale–Short Form (APS-S), sedangkan analisis hasil penelitian menggunakan gain score dan paired sample t-test dengan perangkat lunak JASP. Hasil: Hasil penelitian menunjukkan penurunan signifikan pada skor penundaan dari pretest (M=81,88) ke posttest (M=67,81), dengan p < 0,001. Kesimpulan: Temuan ini menunjukkan bahwa token economy, ketika didukung oleh strategi manajemen waktu seperti Eisenhower Matrix dan penguatan sosial, dapat secara efektif memotivasi mahasiswa untuk menyelesaikan tugas akademik tepat waktu. Pendekatan ini tidak hanya memodifikasi perilaku tetapi juga meningkatkan pengaturan diri (self-regulation) dan rasa tanggung jawab dalam konteks berorganisasi.